Detection of Bartonella henselae DNA in Triatoma sordida collected in peridomiciliary environments - Santos, Luciene Silva Dos; Oliveira, Jader; Mendonça, Vagner José; Rosa, João Aristeu [UNESP]; Maekawa, Alexandre Seiji; Lilioso, Maurício; Silva, Dayane Pires Da; Almeida, Carlos Eduardo; Velho, Paulo Eduardo Neves Ferreira; Drummond, Marina Rovani (Brazilian Society of Infectious Diseases, 2024)
Bartonelloses represent a group of potentially fatal diseases associated with various clinical manifestations including endocarditis. Caused by bacteria belonging to the genus Bartonella, these microorganisms have a remarkable ability to infect mammals, and their transmission is commonly associated with hematophagous vectors such as fleas, lice, mosquitoes, and ticks. The aim of this study was to evaluate the occurrence of Bartonella sp. DNA in 81 triatomines of the species Triatoma sordida collected in the field in peri‑domiciliary areas of the Brazilian city of Seabra, located in the state of Bahia. Nested PCR was conducted targeting the ftsZ gene and real-time PCR targeting the gltA gene, both representing specific reactions for Bartonella henselae. Additionally, conventional PCR targeting kDNA was employed to evaluate the presence of Trypanosoma cruzi. Of the samples tested, 23/81 (28.39 %) bugs showed positive PCR for B. henselae. No sample showed positive PCR for T. cruzi. The high prevalence of triatomines with a positive PCR for B. henselae emphasizes the close relationship between these insects and the bacteria, indicating the need for further studies to investigate the vectorial potential of these kissing bugs.
Keywords: Bartonella henselae; Chagas disease; Endocarditis; Trypanosoma cruzi